Can the Shape of Nanoparticles Enable the Targeting to Cancer Cells over Healthy Cells?. (30th May 2021) - Cong, Vu Thanh; Wang, Wenqian; Tilley, Richard D.; Sharbeen, George; Phillips, Phoebe A.; Gaus, Katharina; Gooding, John Justin
Abstract: Macropinocytosis is a consequence of oncogenic alterations of cancer cells while most healthy cells are non‐macropinocytic. It is currently unclear whether macropinocytic cancer cells can be targeted rather than healthy cells, by adjusting the shape and size of nanoparticles. Herein, the endocytosis of two differently shaped nanoparticles; nanorods and nanospheres are compared in cancer and healthy cells. The cells are breast epithelial cancer cells (MCF7) and breast epithelial healthy cells (MCF10A) and pancreas cancer cells (PANC‐1 cells) and non‐tumourogenic patient‐derived cancer‐associated fibroblasts (CAFs). The endocytosis pathway is quantified by a combination of pair correlation microscopy and endocytosis inhibitors. MCF7 cells use clathrin‐mediated endocytosis and macropinocytosis to take up the nanorods while MCF10A cells use predominantly clathrin‐mediated endocytosis. Based on the comparison of endocytic behavior of cancer and healthy cells, MCF7 cells can be induced to take up more nanorods and suppress the metabolism and endocytosis of nanorods in MCF10A cells. The nanorods allow targeting to breast cancer MCF7 cells and pancreas cancer cells over the healthy cells. This study opens exciting possibilities for shape to target the cancer cells over healthy cells, by adjusting nanoparticle shape. Abstract : The endocytic pathways of two shapes of nanoparticles with cancer and healthy cells are compared. The cancer cells exhibit a strong preference for the nanorods over the nanospheres while the healthy cells show a less dramatic preference for nanorods over nanospheres. Using nanoparticle shape, in combination with chemical inhibitors, it is possible to target cancer cells over healthy cells.